Strategic Innovations to Reshape the Future of Education - Oluokun, Adepeju; Abiodun, Abiola Ayopo; Noor, Alia (Journal of Research, Innovation, and Strategies for Education (RISE), 2026)
In recent decades, educational scholars and practitioners have developed a range of teaching tools, technologies and techniques to improve teaching and learning and to support wider industrial and digital transformations. Despite, despite these advances, many education systems, particularly in developing countries, still struggle to ensure inclusive, equitable and high-quality education in line with the fourth Sustainable Development Goal 4 (SDG 4). Existing studies often focus on isolated initiatives or technologies, but fail to provide a coherent and context-sensitive framework linking strategic innovation in education and training to the wider agenda of the MDGs and SDGs. This review study takes a qualitative and conceptual approach, synthesising evidence from global reports, case studies and academic literature to identify the key challenges and outline a set of strategic, innovative and transformative actions for developing countries. The paper proposes an integrated framework combining digital inclusion, creative curricula design, flexible learning infrastructures, skills-based training, community partnerships and sustainable practices as mutually reinforcing levers for education reform. By explaining how these strategic innovations can be planned, designed and implemented, the study aims to guide policy makers, institutional leaders and practitioners in redesigning education and training systems in developing regions to better prepare learners for their future works and lives, while promoting sustainable socio-economic development.
Keywords: strategic innovation; education and training; Sustainable Development Goal 4 (SDG 4); developing countries; digital transformation; educational sustainability